Doppler indices of middle uterine artery as a tool for predicting the fetal status in cattle with uterine torsion and the recovery of uterine blood flow subsequent to detorsion - SINGH, NAVDEEP; GHUMAN, SARVPREET SINGH; GANDOTRA, VINOD KUMAR (The Indian Journal of Animal Sciences, 2019)
The aim was assessment of blood flow to uterus in cattle suffering from uterine torsion as a tool for predicting the fetal survivability after detorsion. Dairy cattle (14) with uterine torsion were detorted and fetal delivery was completed within 30 min after detorsion. Doppler sonography of middle uterine artery ipsilateral (IpsiUA) and contralateral (ContUA) to the side of torsion was carried out before uterine detorsion and 30 min after fetal delivery for Doppler indices, viz. blood flow volume (BFV), time-averaged peak velocity (TAP), resistance index (RI) and pulsatility index (PI). Before uterine detorsion, RI-IpsiUA and PI-IpsiUA were high in comparison to their values in ContUA. Although RI-IpsiUA and PI-IpsiUA had difference between their values before uterine detorsion and 30 min after fetal delivery, but in contrast, at the same time point, there was no difference in RI-ContUA and PIContUA. In comparison to RI-IpsiUA and PI-IpsiUA before detorsion, their respective values decreased after fetal delivery subsequent to successful detorsion, and were almost similar to their respective post-fetal delivery RIContUA and PI-ContUA. In cases where fetus after detorsion of uterus was delivered dead, in the middle uterine artery ipsilateral to the side of uterine torsion, BFV-IpsiUA and TAP-IpsiUA were low, whereas PI-IpsiUA were high. In conclusion, depicting the blood flow within middle uterine artery using Doppler sonography could be helpful in predicting the viability of fetus in uterine torsion affected cattle and may confirm the resumption of blood flow to uterus subsequent to detorsion.